2013
DOI: 10.1111/jnc.12131
|View full text |Cite
|
Sign up to set email alerts
|

Activity‐dependent secretion of alpha‐synuclein by enteric neurons

Abstract: There is growing evidence supporting a role of extracellular alpha-synuclein in the spreading of Parkinson's disease (PD) pathology. Recent pathological studies have raised the possibility that the enteric nervous system (ENS) is one of the initial sites of alpha-synuclein pathology in PD. We therefore undertook this survey to determine whether alphasynuclein can be secreted by enteric neurons. Alphasynuclein secretion was assessed by immunoblot analysis of the culture medium from primary culture of ENS. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 19 publications
4
70
0
4
Order By: Relevance
“…The data suggest that growth and differentiation of postnatal enteric neurons promoted by GDNF involves a concomitantly increased gene expression of a-syn required for the functional integrity of enteric neuronal networks. This observation is in line with data described by Paillusson et al (2013) who reported that a-syn can be secreted by enteric neurons in an activity-dependent fashion.…”
Section: A-syn and Synaptophylsin In Myenteric Plexus Culturessupporting
confidence: 93%
“…The data suggest that growth and differentiation of postnatal enteric neurons promoted by GDNF involves a concomitantly increased gene expression of a-syn required for the functional integrity of enteric neuronal networks. This observation is in line with data described by Paillusson et al (2013) who reported that a-syn can be secreted by enteric neurons in an activity-dependent fashion.…”
Section: A-syn and Synaptophylsin In Myenteric Plexus Culturessupporting
confidence: 93%
“…These primary cultures have been derived from rat, mouse, flies and even from human embryonic stem cells (Park and Lee, 2006;Rideout et al, 2004;Zhou et al, 2002Zhou et al, , 2000. Besides the species, also the region of the nervous systems from which the cell derive can vary from study to study, cerebellar granular cells (Monti et al, 2007), dorsal root ganglia , cortical and midbrain neurons (Rideout et al, 2003) and enteric neurons (Paillusson et al, 2013) just to name a few.…”
Section: Cellular Models Of Alpha-synuclein Pathology And/or Spreadingmentioning
confidence: 99%
“…Кроме того, в микробиоте кишечника пациентов с болезнью Паркинсона отмечается повышение представленности бактерий, способ-ных оказывать влияние на работу нейронов. Так Lactobacillus mucosae, содержание которой в ми-кробиоте кишечника повышается как в сравнении с другими неврологическими заболеваниями, так и при сравнении с группой здорового контроля на финской популяции [7], способна влиять на секрецию α-синуклеина через взаимодействия с нейронами кишечника [33,34]. Кроме того, одно из производных β-индолилуксусной кислоты, вы-деляемой ранее упоминавшийся Intestinibacter bartlettii, -5-гидроксииндолилуксусная кислота -является метаболитом серотонина и способно оказывать влияние на работу нервной системы, в частности понижать болевой порог [35].…”
Section: оригинальные статьиunclassified